Early statin therapy in patients with acute intracerebral hemorrhage without prior statin use. (26th January 2015) - Chen, P.‐S.; Cheng, C.‐L.; Chang, Y.‐C.; Kao Yang, Y.‐H.; Yeh, P.‐S.; Li, Y.‐H.
<x xml:space="preserve">Abstract</x> Background and purpose Statin therapy is beneficial for primary and secondary prevention of ischaemic stroke, but its influence in patients with intracerebral hemorrhage (ICH) is unclear. An assessment was made of the effect of early statin therapy on patients with acute ICH. Methods Taiwan's National Health Insurance Research Database was screened for patients without prior statin therapy admitted from January to December 2008 for newly diagnosed ICH. Patients taking statins during hospitalization or within 3 months post‐discharge were the early statin group (n = 749); patients who were not were the control group (n = 7583). The study end‐points were recurrent ICH and all‐cause mortality during follow‐up. Results All eligible patients were followed up until 31 December 2010. During the follow‐up, 69 (9.2%) patients in the early statin group and 677 (8.9%) control group patients had recurrent ICH. Cox proportional hazards analyses showed that early statin use did not increase the risk of recurrent ICH (adjusted hazard ratio 1.044; 95% confidence interval 0.812–1.341). During the same period, 90 (12.0%) of the early statin group and 1519 (20.0%) control group patients died. All‐cause mortality was lower in the early statin group (adjusted hazard ratio 0.742; 95% confidence interval 0.598–0.919) than in the control group. Matched propensity score analyses were consistent with findings in Cox proportional hazards analyses. Conclusions Early statin group patients with acute ICH did not have a higher recurrent risk of ICH and might have lower all‐cause mortality during follow‐up. It is concluded that statin therapy might be beneficial for patients with ICH.